Democracy and social policies for inequality reduction in Brazil : representatives policies' congruence and relevance – 1998-2018 - Cruz, Rafael Georges da (2019)
Tese (doutorado)—Universidade de Brasília, Instituto de Ciência Política, Programa de Pós-Graduação em Ciência Política, 2019.